Finite element analysis of 3D structure wing box test rig / Hasbolah Mohd Said - Mohd Said, Hasbolah (2010)
Wing box test rig is designed to hold the wing in place and keep them cantilevered so that the lift on the wing doesn't deform the test rig during experimental session. In order to conduct a test that involve high load, the design of the wing box test rig structure need to be constructed. The purposes of this project are to study on designing and conducting finite element analysis of the wing box test rig for static test experiment. There are several consideration to be emphasizes such as load requirement, structural stability and using finite element modeling software, the test rig is designed, simulated and analyzed in the computer. The finite element analysis modeling software that is used in this project is ANYSY/ED 12.1. During the simulation, the structural analysis data such as deformation of beam and the stress distribution were determined. The material used for this project is mild steel A36 and two different beams were selected then will be compared. Results obtained from study using ANSYS software were then compared with the result obtained from the theoretical analysis. Finally, the design alteration needs to be done to counter any problenf in analysis. From this study, it is expected that this project can help another student as reference to manufacture the whig box test rig in a future.